IMPLEMENTASI PERENCANAAN PENDIDIKAN DALAM LEMBAGA PENDIDIKAN ISLAM - Kasmawati Kasmawati (Idaarah: Jurnal Manajemen Pendidikan, 2019)
Planning basically determines the activities to be carried out in the future. Tihis activity is itended to regulate various resources so that the results achieved are as expected. Pallning management is an act of determining in advance what will be done, how to do it, what to do and who does it. Palnning is often also a bridge that connect gaps or gaps between the present state and the conditions expected to occur in the future. Although the right state of the future si difficult to predict, because many factors beyond human mastery have an affevt on the paln. But, without planning we will surrender the situation in the future to a coincidence.